2015
DOI: 10.1111/wrr.12265
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of wound healing signaling as a potential therapeutic target for radiation‐induced tissue damage

Abstract: We hypothesized the histone deacetylase inhibitor phenylbutyrate (PB) has beneficial effects on radiation-induced injury by modulating the expression of DNA repair and wound healing genes. Hamsters received a radiosurgical dose of radiation (40 Gy) to the cheek and were treated with varying PB dosing regimens. Gross alteration of the irradiated cheeks, eating function, histological changes, and gene expression during the course of wound healing were compared between treatment groups. Pathological analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Improvement of wound healing by application of PDGF to radiation-damaged tissue was not observed in this study. Radiation exerts a negative effect on the mitogenic potential of PDGF [46]; thus, the normal function of PDGF could have been impaired in irradiated skin. Early treatment of radiation-induced skin ulceration can lessen pain and reduce secondary infection and damage of adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of wound healing by application of PDGF to radiation-damaged tissue was not observed in this study. Radiation exerts a negative effect on the mitogenic potential of PDGF [46]; thus, the normal function of PDGF could have been impaired in irradiated skin. Early treatment of radiation-induced skin ulceration can lessen pain and reduce secondary infection and damage of adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that CRT can increase tissue reactive oxygen species (ROS), leading to excessive oxidative stress, tissue destruction, and even toxicity [9,27,28]. We deduced that excessive ROS and oxidative stress may be one of the reasons for the increased AL after preoperative CRT.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…It has been reported that radiation can generate free radicals or reactive oxygen species (ROS), leading to oxidative stress [8]. The ROS generated by ionizing radiation and excessive oxidative stress can initiate DNA and non-DNA damage, oxidize lipids and proteins, and even cause tissue damage [9,10]. Additionally, the generation of ROS and their by-products was considered to mediate the cytotoxic effects of chemotherapy, which may lead to cell damage [11].…”
Section: Introductionmentioning
confidence: 99%
“…105 The pharmacological functions of the major listed HDAC inhibitors are summarized in Table 2. [106][107][108][109][110][111][112][113][114][115] Vorinostat, the first FDAapproved HDAC inhibitor, was approved for the treatment of cutaneous T-cell lymphoma (CTCL). Vorinostat belongs to the hydroxamic acid class of inhibitors, and its targets include class I, II, and IV HDACs.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%